Cooperative Effects in Heterometallic Complexes. Issue 61 (21st October 2021) - Prosenc, Marc H.; Kappes, Manfred M.; Niedner‐Schatteburg, Gereon
Abstract : 3MET : In this Guest Editorial, M. H. Prosenc, M. M. Kappes, and G. Niedner‐Schatteburg, present the latest work from the transregional collaborative research center 3MET.de founded in 2009 and located at the TU Kaiserslautern (TUK) and at the Karlsruhe Institute of Technology (KIT).